High thermoelectric figure of merit in monolayer Tl2O from first principles - Huang, Qingjun; Ma, Jinlong; Xu, Dongwei; Hu, Run; Luo, Xiaobing (Journal of applied physics, 2020)
The thermoelectric properties of monolayer Tl 2 O are studied using first-principles calculations with all involved electrical and thermal transport properties calculated in the parameter-free frameworks. It is found that monolayer Tl 2 O possesses remarkably high thermoelectric figure of merit, z T, due to its ultralow lattice thermal conductivity and fairly good power factor. The room temperature z T can be as high as 1.4 and 1.2 for n- and p-type systems, respectively, whereas the maximum z T values can reach up to 5.3 and 4.2 as the temperature increases to 800 K. In addition, it is clarified that the mobilities of monolayer Tl 2 O are orders of magnitude smaller than previous estimation from simplified semiempirical models. The room temperature electron and hole mobilities are only about 56 and 11 cm 2 V − 1 s − 1, respectively, due to the heavy effective mass along with strong polar optical phonons coupling scattering. Nonetheless, the intrinsically ultrahigh z T from entire first-principles calculations stimulate that the further experimental verification and exploration for practical application are worthwhile.